DIGITAL MARKETING STRATEGY, SERVICE QUALITY, AND CUSTOMER ENGAGEMENT: INVESTIGATING THE MEDIATING EFFECT OF CUSTOMER EXPERIENCE IN ASTRO’S QUICK COMMERCE PLATFORM - Rangga Aditya Pratama; Nur Hayati (RADJA PUBLIKA, 2026)
The accelerated expansion of quick commerce has sharpened rivalry among digital retail platforms, compelling business actors to formulate robust marketing approaches and ensure excellent service performance in order to sustain customer involvement. This study was undertaken to examine the degree to which digital marketing strategy and service quality contribute to customer engagement, while also assessing the explanatory role of customer experience in linking these variables among users of ASTRO’s 24-hour quick commerce service in Indonesia. A quantitative explanatory research design was employed, utilizing survey data gathered from 285 active ASTRO users who had completed transactions during the preceding three months. The collected data were processed using PLS-SEM. The findings reveal that digital marketing strategy exerts a significant effect on customer experience (β = 0.578, p < 0.001), and service quality likewise produces a positive and significant influence on customer experience (β = 0.406, p < 0.001). In addition, customer experience is shown to have a significant impact on customer engagement (β = 0.449, p < 0.001). Digital marketing strategy and service quality are also proven to make meaningful contributions to customer engagement, while customer experience serves as a key mechanism in clarifying customer behavioral responses. These results emphasize the necessity of harmonizing well-directed digital marketing efforts with reliable service delivery to generate favorable customer experiences and reinforce customer engagement. This study enriches the expanding body of scholarship on digital marketing and consumer behavior in the quick commerce sector, while offering managerial implications for strengthening customer relationships within increasingly competitive digital business environments.